2022
DOI: 10.4103/ijc.ijc_786_19
|View full text |Cite
|
Sign up to set email alerts
|

Results of radiotherapy in squamous cell laryngeal cancer

Abstract: Background: Laryngeal cancer is a common type of head and neck cancer (HNC). Radiotherapy (RT) is a mainstay for curative treatment. Intensity-modulated RT (IMRT) is a standard technique today, as it provides of higher survival and local control and lower normal tissue toxicity. One of IMRT devices is helical tomotherapy (HT). The HT treatment results of HNC patients have been reported in few studies. We aimed to investigate the results of squamous cell laryngeal carcinoma patients treated with hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A prospective study conducted by Chatterjee et al revealed favorable outcomes, with 5-year local recurrence-free survival rate of 75.1% using helical radiotherapy for early-stage laryngeal cancers [ 13 ]. Bolukbas et al investigated 45 patients with laryngeal cancer at any clinical stage, all of whom were treated with helical tomotherapy [ 14 ]. They reported that the 3-year OS and DFS rates were 71.7% and 60.4%, respectively, with acceptable radiation-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prospective study conducted by Chatterjee et al revealed favorable outcomes, with 5-year local recurrence-free survival rate of 75.1% using helical radiotherapy for early-stage laryngeal cancers [ 13 ]. Bolukbas et al investigated 45 patients with laryngeal cancer at any clinical stage, all of whom were treated with helical tomotherapy [ 14 ]. They reported that the 3-year OS and DFS rates were 71.7% and 60.4%, respectively, with acceptable radiation-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Bolukbas et al also investigated the use of helical tomotherapy for treating 45 patients with LSCC. Their results indicated that the 3-year OS and DFS were 71.7% and 60.4%, respectively [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation